ANALISIS MISKONSEPSI SISWA MENGUNAKAN PENDEKATAN KOGNITIF DALAM MATERI USAHA DAN ENERGI SISWA SMA NEGERI 1 KUPANG - Sukarjita, I Wayan; Lantik, Vinsensius; Takel, Jen Melindi B.A (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2023)
Misconception is one of the causes of a student's learning difficulties. This study aimed to obtain information about whether there were students' misconceptions about work and energy and the factors that caused these misconceptions. The population of this research is class X Negeri 1 Kupang students. The data collection technique used in this study was a written test instrument with multiple choices, totaling 10 questions and documentation. This research method uses quantitative research with research data consisting of quantitative data and qualitative data. The subjects of this study were class X SMA Negeri 1 Kupang students. Data collection methods include tests and documentation of student work. The four-tier diagnostic test consists of 4 levels: questions with answer choices, choice of answer confidence level, choice of reasons, and choice of confidence level of reason. The results of the study show that the category of misconceptions about work and energy by students of SMA Negeri 1 Kupang is in the moderate category.